2017
DOI: 10.1111/jonm.12495
|View full text |Cite
|
Sign up to set email alerts
|

Patient acuity and nurse staffing challenges in Norwegian neonatal intensive care units

Abstract: Planning for reduced staffing for weekends and summer seasons is ineffective. Staffing planned for most of the days in a year instead of the median need for nurses will result in a greater increase in the need for nurses in small units compared to larger units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…With regard to seasonality, NSLs (patients per nurse) are higher during the summer season ( M = 11.34; SD = 3.6). This might reflect the decrease in recruitment during the vacation period in hospitals, despite scientific evidence that there is no drop in demand for nursing during summer vacation vs. the rest of the year (Ohnstad & Solberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to seasonality, NSLs (patients per nurse) are higher during the summer season ( M = 11.34; SD = 3.6). This might reflect the decrease in recruitment during the vacation period in hospitals, despite scientific evidence that there is no drop in demand for nursing during summer vacation vs. the rest of the year (Ohnstad & Solberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that shift patterns could range from 8.94 patients per nurse on morning shifts to 12.4 patients per nurse on evening or night shifts. This traditional shift pattern (50% in the morning, 30% in the evening, and 20% at night) is based on projected activity levels of nurses over a three‐shift pattern, but takes scant account of the fluctuating demand and dependency of care and patient status (Ohnstad & Solberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many observational studies have estimated the number of nurses needed in a unit based on estimates of patient acuity levels. For example, one study estimated the number of nurses needed in a neonatal intensive care unit (NICU) by assigning nurse ratios based on a five‐level acuity scale (Ohnstad & Solberg, 2017). However, as this study demonstrates, these ratios can provide erroneous estimates of true nurse staffing.…”
Section: Discussionmentioning
confidence: 99%
“…Because patient acuity levels may decrease during weekends, evenings, and holidays, 49,50 some hospital administrations lower nurse staffing levels during these times. However, when staffing nurses by patient acuity rather than by day of the week or season, researchers have found that staffing levels should be maintained, not lowered, to enhance patient safety 51 . Similarly, De Cordova et al 26 noted that patients were more likely to have a longer hospital LOS when staffing levels were lower during nightshift compared to dayshift 24 .…”
Section: Introductionmentioning
confidence: 99%